Failure mechanism and stability analysis of an open-pit slope under excavation unloading conditions - Wang, Jianming; Zhou, Zihan; Chen, Chong; Wang, Huan; Chen, Zhonghui (Frontiers in Earth Science, 2023)
Excavation unloading significantly contributes to rock slope failure in an open-pit mine. At present, there is no relevant theoretical study on the failure mechanism of the rock slope under excavation unloading. Therefore, here, based on the theory of fracture mechanics, the expression of stress intensity factor at the crack tip in the rock mass at the vertical distance, h, from the slope top under excavation unloading is derived, the calculation method of crack initiation angle is given, the expression of the ultimate safe height of the slope under unloading is obtained, and the ratio of the fracture toughness of the slope rock mass to the composite stress intensity factor at the crack tip in the rock mass is defined as the slope stability factor, which is verified by an engineering example. The results show that the crack initiation angle decreased with increased crack inclination, and the crack initiation angle increased with increased side pressure coefficient, slope angle, and friction coefficient. The ultimate safety height of the slope decreased first and then increased with the increase of the crack angle, and it was approximately linear with the crack length and inversely proportional with the slope angle. The stability coefficient calculated by this method is the same as that calculated by the limit equilibrium method and is small, which indicates the accuracy and rationality of this method. Results here can provide a theoretical basis for understanding and controlling the slope collapse disaster induced by excavation unloading.unloading.